Artificial Intelligence (AI) Adoption as Marketing Tools among Micro, Small, and Medium Enterprises (MSMEs) in Indonesia - Santosa, Allicia Deana; Surgawati, Iis (Institut Teknologi Sepuluh Nopember, 2024)
Despite MSMEs' crucial role in Indonesia's economy, their utilization of artificial intelligence (AI) remains restricted. This paper investigates the adoption of artificial intelligence (AI) among micro, small, and medium enterprises (MSMEs) in Indonesia, providing a comprehensive analysis of the difficulties and potential advantages. AI implementation is essential for these businesses because it may significantly enhance economic growth through improved productivity, cost reduction, and increased competitiveness. Furthermore, AI facilitates the decision-making process and fosters data-based innovation. The study investigates the correlation between competitive pressure, top management commitment, staff adaptability, perceived utility, and simplicity of use in the adoption of artificial intelligence (AI) among micro, small, and medium enterprises (MSMEs) in Indonesia. By addressing these gaps, we can enhance our comprehension of how MSMEs can utilize AI adoption as a marketing tool, thereby fostering their growth and success. The results emphasize the significance of top management commitment (TMC), employee adaptability (EA), perceived usefulness (PU), and perceived ease of use (PEOU) in encouraging the adoption of AI among micro, small, and medium enterprises (MSMEs) in Indonesia.